Surgical treatment of chondrosarcoma of the sacrum with cement augmentation: A case report - Liu, Shuzhong (Medicine (Baltimore), 2019)
RATIONALE: Chondrosarcoma of the sacrum is a highly unusual disease without standard curative managements yet. The objective of this study is to report a very rare case of chondrosarcoma of the sacrum successfully operated by percutaneous vertebroplasty. The management of these unique cases has yet to be well-documented. PATIENT CONCERNS: A 45-year-old woman presented with a five-month history of continuous and progressive pain and numbness of left extremity. A lytic, expanding lesion of the sacrum and paraspinal region with severe epidural spinal cord compression was identified. DIAGNOSIS: MRI of spine showed spinal cord compression secondary to the epidural componant of the giant mass, with increased marrow infiltration of the left S2 vertebral and paravertebral region, which presented as a solid tumor. Post-operative pathology confirmed the diagnosis of sacral well-differentiated chondrosarcoma (stage I B). INTERVENTIONS: The patient underwent percutaneous vertebroplasty and cement augmentation of sacrum via a posterior approach. OUTCOMES: The patient's neurological deficits improved significantly after the surgery, but the patient died of multiple systemic metastases at the 2-year follow-up visit. There were no complications associated with the operation during the follow-up period. LESSONS: Taken together, the lesion's clinical features, imaging results, and pathological characteristics are unique. Combined efforts of specialists from orthopedics, radiology, neurosurgery, pathology, and medical oncology led to the successful diagnosis and management of this patient. Giant sacral chondrosarcoma, although rare, should be part of the differential diagnosis when the patient presents with back pain and radiculopathy. We recommend the posterior approach for spinal decompression of the sacral chondrosarcoma when the tumor has caused neurological deficits or other severe symptoms. Osteoplasty by cement augmentation is also a good choice for surgical treatment.